Trends in Chitosan as a Primary Biopolymer for Functional Films and Coatings Manufacture for Food and Natural Products - Díaz-Montes, Elsa (Polymers (Basel), 2021)
Some of the current challenges faced by the food industry deal with the natural ripening process and the short shelf-life of fresh and minimally processed products. The loss of vitamins and minerals, lipid oxidation, enzymatic browning, and growth of microorganisms have been the main issues for many years within the innovation and improvement of food packaging, which seeks to preserve and protect the product until its consumption. Most of the conventional packaging are petroleum-derived plastics, which after product consumption becomes a major concern due to environmental damage provoked by their difficult degradation. In this sense, many researchers have shown interest in edible films and coatings, which represent an environmentally friendly alternative for food packaging. To date, chitosan (CS) is among the most common materials in the formulation of these biodegradable packaging together with polysaccharides, proteins, and lipids. The good film-forming and biological properties (i.e., antimicrobial, antifungal, and antiviral) of CS have fostered its usage in food packaging. Therefore, the goal of this paper is to collect and discuss the latest development works (over the last five years) aimed at using CS in the manufacture of edible films and coatings for food preservation. Particular attention has been devoted to relevant findings in the field, together with the novel preparation protocols of such biodegradable packaging. Finally, recent trends in new concepts of composite films and coatings are also addressed.